Identifying African American Women with HIV Infection in an Expanded HIV testing and Linkage to Care (X-TLC) Program in Healthcare Settings on the South and West Sides of Chicago. (4th October 2017) - McNulty, Moira C; Almirol, Ellen; Ridgway, Jessica P; Schmitt, Jessica; Eavou, Rebecca; Taylor, Michelle; Kern, David; Schuette, Stephanie; Stonehouse, Patrick; Tobin, Audra; Glick, Nancy; Pitrak, David
Abstract: Background: Women account for 25 % of HIV infections nationally, and African American (AA) women are disproportionately affected. We report important gender differences observed in an expanded HIV testing and linkage to care (X-TLC) program conducted on the South and West Sides of Chicago. Methods: X-TLC is funded by CDPH with CDC prevention B funds. X-TLC has expanded from 3 sites to 14 sites, including acute care hospitals (academic, community), community health centers (CHCs), and family planning clinics. We report descriptive stats, group comparisons by Chi-square, and multivariate analyses adjusted for demographics. Results: Since 2011, X-TLC has conducted 308, 038 HIV screens, and 63.7 % of those tested were women. Overall seroprevalence for HIV was 0.56 %, and 30.5 % of HIV patients identified were cis-gender women (seroprevalence 0.15 %). The seroprevalence for women testing in EDs was higher (0.44 %). Similar to men, only 52.9 % of HIV positive women were new diagnoses. Women accounted for 28.5 % of all new diagnoses, compared with 15.4 % for Chicago overall. In 2016 X-TLC screened 91, 865 persons for HIV, and 65.2 % of those tested were women. There were 193 new diagnosis and 32.1 % (62) were women, 85.7 % AA. In comparison, in 2015 there were 139 women with a new HIV diagnosis for all of Chicago. Women newly diagnosed were less likely to be linked to care (adjusted odds ratio, aOR, 0.54, 0.35–0.85). Linkage was lower for women diagnosed at CHCs (84.6 % vs. 76.3 %, P = 0.02). Most CHCs did not have on site HIV providers. At our site, however, women linked to care were more likely to be retained in care (aOR 0.58, 0.43–0.78). We also conduct targeted outreach testing, partner services (PS) testing, and social network strategy (SNS) testing, but women are not identified by these programs (16/171 tested women, 8 new diagnoses were men for PS; 507 tested, 471 men and 36 trans-gender women, 38 new positives, 0 cis-gender women for SNS). Conclusion: More women than men were offered and/or accept HIV screening in healthcare settings. The proportion of seropositive women identified was higher than the national average. X-TLC is reaching a large proportional of AA women with HIV unaware of their status. Other testing strategies will rarely identify cis-gender women with HIV infection. Gender differences in linkage to and retention in care will require strategies targeted at women. Disclosures: J. P. Ridgway, Gilead FOCUS: Grant Investigator, Grant recipient; N. Glick, Gilead FOCUS: Grant Investigator, Grant recipient; D. Pitrak, Gilead Sciences FOCUS: Grant Investigator, Grant recipient